Empowering Women Entrepreneurs' Good Health and Well-Being through Education and Access to Quality Healthcare - Agustin Pratama Sari, Dewi; Firdausi Rachmadania, Rizki; Iranto, Dicky; Hasanah, Nuramalia; Takidah, Erika; Aminah, Hania; Ikhwan, Muhammad; Al Finsih, Muhamad; Jofarhan, Muhammad; Hidayat, Nur (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
Nowadays, business opportunities are wide open, including for women who are usually marginalized. Being a female entrepreneur certainly has its own challenges. The challenges will be even greater if women also act as wives and mothers. PPUMI Women's community, often face the problems that women with multiple roles have difficulty finding balance in dividing their time between work, family and themselves. Often their mental and physical health is disturbed. In fact, to increase one's capabilities so that one can carry out tasks with various roles carried out in social life, awareness is needed to care for and maintain one's own sanity. Therefore, the UNJ Community Service team aims to holding seminars and online consultations regarding women's empowerment so that they can grow their mental and mental capacity in balancing multiple or more roles in social life in society. The invited speakers are expert speakers who have experienced similar problems but have succeeded in growing their capacity and ability to deal with them with total number of participants are more than 30. We hope that the target partners for this community service can experience the same thing and continue to grow.